Optimization of Printed TIPS-Pentacene Thin-Film Applied on OFET technology - Martins, Carla Sofia Gonçalves (2017)
The area of Printed Electronics is relatively new, but promises to make a revolution in several applications, particularly in smart cards and radio-frequency identification devices (RFIDs). However, to achieve this goal is of fundamental importance to progress towards printed transistors and complementary circuits. In this sense, this thesis aims to advance the research on printing Organic Field-Effect Transistors (OFETs), both ptype and n-type. The first step was to dominate the processing technique of thin films composed by TIPS-Pentacene (a p-type molecule), as well as to adjust the parameters of its solution to produce suitable electronic ink for inkjet printing. Other important step was to treat the surface dielectric layer, which is as important as the semiconductor layer for a good performance of an OFET. We choose poly(methyl metacrilate) (PMMA) as the insulator material. A detailed study of the morphology of printed TIPS-Pentacene was also carried out. After the deposition of the dielectric and the semiconductor layers, which showed good crystallinity index, we characterized the p-OFET and built a pMOS inverter, which shows to be promising in logical circuits. With these results in mind, the next step is to build a CMOS inverter-TIPS Pentacene / P(NDI2OD-T2) and thus pave the way for the manufacture of a complementary circuit.